O pão e a festa: patrimônio imaterial e turismo em Juiz de Fora - Almeida, Patricia Lage de (2015)
This research aims to analyze the application to register the German bread and Deutsches Fest as immaterial cultural assets belonging to Juiz de Fora city as representative elements of immigrants' culture and tradition, those who took part of the history of the city. The German Party or Deutsches Fest is currently one of the most important events in the cultural and tourist calendar of Juiz de Fora, a city located in Zona da Mata, state of Minas Gerais. It takes place at a neighborhood called Borboleta and it was first held in 1969 by German descendants who have immigrated to the city during the mid-nineteenth century. The German Bread, which can be found in parties and in houses of the neighborhood, besides being the main tool to memory preservation built by these German descendants, it became a significant symbolic element, concerning preparation method of legitimate German food. Bread and Party were part of an identity built over the years to set up the group, allowing them to broaden their participation in local political and economic contexts.